2020
DOI: 10.1002/acn3.51041
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain in FTLD: association with C9orf72, clinical phenotype, and prognosis

Abstract: ObjectiveThe aim of the present study was to compare the levels of serum neurofilament light chain (sNfL) in frontotemporal lobar degeneration (FTLD) patients of different clinical subtypes (bvFTD, PPA, and FTLD‐MND) and with or without the C9orf72 repeat expansion, and to correlate sNfL levels to disease progression, assessed by the brain atrophy rate and survival time.MethodsThe sNfL levels were determined from 78 FTLD patients (C9orf72 repeat expansion carriers [n = 26] and non‐carriers [n = 52]) with Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…There are limited number of studies comparing p-Tau181 between AD and FTD. Apart from p-Tau181, p-Tau217 has also been investigated both in CSF [ 51 ] and in plasma [ 52 ]. From these findings, plasma p-Tau217 differentiated AD from FTD and other neurodegenerative diseases, and may show higher accuracy than p-Tau181.…”
Section: Resultsmentioning
confidence: 99%
“…There are limited number of studies comparing p-Tau181 between AD and FTD. Apart from p-Tau181, p-Tau217 has also been investigated both in CSF [ 51 ] and in plasma [ 52 ]. From these findings, plasma p-Tau217 differentiated AD from FTD and other neurodegenerative diseases, and may show higher accuracy than p-Tau181.…”
Section: Resultsmentioning
confidence: 99%
“…68 The invasive nature and reduced patient acceptability of lumbar puncture has led to interest in blood-based assays for the quantification of NfL, which are highly correlated with CSF levels, and have similarly been shown to correlate with disease severity and predict survival in FTLD. 69,70,71,72 Tau CSF tau is another biomarker with growing utility in the diagnosis and prediction of survival in dementia syndromes, with particularly robust evidence in AD. 73 Results of tau levels in FTLD are more variable, potentially due to the heterogenous neuropathology of FTLD (e.g.…”
Section: Neurofilament Light Chainmentioning
confidence: 99%
“…In this regard, few studies showed an association between high CSF NfL levels and rapid cognitive decline in AD's mild cognitive impairment stage (Zetterberg et al, 2016;Pillai et al, 2020). Similarly, in the FTD spectrum, higher basal CSF and/or blood NfL values have been related to faster disease progression (in some clinical syndromes) (Ljubenkov et al, 2018;Rojas et al, 2018) and shorter survival (Meeter et al, 2018;van der Ende et al, 2019;Benussi et al, 2020;Cajanus et al, 2020), suggesting the utility of an early NfL assessment in the prediction of future disease aggressiveness.…”
Section: Other Neurodegenerative Dementiasmentioning
confidence: 99%